Multifocal congenital hemangioma: Expanding the pathogenesis of "neonatal hemangiomatosis". Issue 5 (23rd June 2019) - Blumenthal, Shoshana; Stefanko, Nicole; Cossio, Maria‐Laura; Coulombe, Jerôme; McCuaig, Catherine; Dubois, Josee; North, Paula; Drolet, Beth
Abstract: Congenital hemangiomas are benign vascular tumors, categorized by their postnatal behavior as rapidly involuting, non‐involuting, or partially involuting. They are typically solitary, with a predilection for the head or limbs near a joint. We present two infants with small, multifocal congenital nonprogressive hemangiomas of the skin, one associated with hepatic and intracranial lesions, and another with an in utero intracranial hemorrhage and hydrocephalus. These cases further extend the differential diagnosis of congenital multifocal vascular lesions or "hemangiomatosis."